PENGARUH PENERAPAN BAHAN AJAR BERBASIS KARAKTER MELALUI MODEL PEMBELAJARAN POE TERHADAP HASIL BELAJAR SISWA KELAS XI SMAN 5 PADANG - Siti Riva Darwata; Yenni Darvina; Masril Masril (Universitas Negeri Padang, 2015)
Student learning outcomes are not optimal due to the model of learning and teaching materials used are less varied and no load values of character. Therefore, researchers are trying to use teaching materials with a character-based learning model POE (Prediction, Observation, Explanation) to improve student learning outcomes. This research is a Quasi Experiment Research with Randomized Control Group Only Design. The study population was a class XI student of SMAN 5 Padang listed in the Academic Year 2014/2015. Sampling was done by purposive sampling technique. Research data collection in the form of a written test for competency knowledge and competency observation sheet for scoring rubric for the attitude and skill competencies. Research data analysis techniques using t-test at the 0.05 significance level for all three competencies. Based on the analysis of data it can be concluded the application of teaching materials through a character-based learning model POE (Prediction, Observation, Explanation) the learning outcomes of students of class XI SMAN 5 Padang effect to aspects of knowledge competence and attitude but not to competence skills